The Design and Implementation of Level Shifted SPWM for 3-Phase 3-Level Inverter : Optimization for Renewable Energy Applications - Al-Khansa, Ahmad Qurthubi Salman; I Made Wiwit Kastawan; Nanang Mulyono (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2025)
The use of renewable electrical energy aims to meet increasing energy needs. One form of electrical energy from renewable sources includes Direct Current (DC) voltage. On the other hand, many household and industrial appliances require Alternating Current (AC) voltage. Therefore, an inverter device is required to convert the (DC) voltage into (AC). The use of inverters may cause high harmonic values of voltage and current in the power grid. The selection of the right switching technique and inverter level can reduce the harmonic value. This research aims to produce a module that can issue a signal to trigger 3 levels of 3-phase inverter using the level-shifted SPWM switching method. The design and implementation of the level-shifted SPWM module uses analog signal processing. Level-shifted SPWM works using two carrier signals, which are then compared with the 3 phase sinusoidal reference signal. In this research, a level-shifted SPWM module for 3 levels of 3-phase is produced, having an output of 12 SPWM level-shifted signals, with multi carrier signals frequency that can be varied from 500-2500 Hz and a reference signal that is fixed at 50 Hz. The output voltage ranging from 10-11 Volt DC